Local resource competition and local resource enhancement shape primate birth sex ratios - Silk, Joan B (The Royal Society, 2008)
Sex ratio theory provides a powerful source of testable predictions about sex allocation strategies. Although studies of invertebrates generally support predictions derived from the sex ratio theory, evidence for adaptive sex ratio biasing in vertebrates remains contentious. This may be due to the fact that most studies of vertebrates have focused on facultative adjustment in relation to maternal condition, rather than processes that might produce uniform sex biases across individuals. Here, we examine the effects of local resource enhancement (LRE) and local resource competition (LRC) on birth sex ratios (BSRs). We also examine the effects of sex differences in the costs of rearing male and female offspring on BSRs. We present data from 102 primate species and show that BSRs are skewed in favour of the dispersing sex in species that do not breed cooperatively, as predicted by the LRC model. In accordance with the LRE model, BSRs are generally skewed in favour of the more beneficial sex in cooperatively breeding primate species. There is no evidence that BSRs reflect the extent of sexual size dimorphism, an indirect measure of the costs of rearing male and female offspring. These analyses suggest that adaptive processes may play an important role in the evolution of BSRs in vertebrates.